엄정한 양형을 위한 유죄인정감형제도의 활용 - 김정욱 (12969, 2013)
This paper outlines the findings of a model of plea bargaining with multiple defendants, in which a prosecutor makes plea offer sequentially. It is shown that plea discount can be minimized with sequential offers and that not all of defendants shall be in